1997
DOI: 10.1016/s0092-8674(00)80339-6
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Anoikis: MEKK-1 Activation Requires Cleavage by Caspases

Abstract: Certain cell types undergo apoptosis when they lose integrin-mediated contacts with the extracellular matrix ("anoikis"). The Jun N-terminal kinase (JNK) pathway is activated in and promotes anoikis. This activation requires caspase activity. We presently report that a DEVD motif-specific caspase that cleaves MEKK-1 specifically is activated when cells lose matrix contact. This cleavage is required for the activation of the kinase activity. When overexpressed, the MEKK-1 cleavage product stimulates apoptosis; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
347
2

Year Published

1998
1998
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 483 publications
(365 citation statements)
references
References 31 publications
16
347
2
Order By: Relevance
“…Here, we show that overexpression of p27 Kip1 in leukemic cells growing in suspension delays druginduced apoptosis and cytotoxicity, indicating that neither intercellular adhesion nor adherence to extracellular matrix (Cardone et al, 1997) are necessary for p27 Kip1 to prevent cell death. We also demonstrate that p27 Kip1 overexpression prevents the activation of procaspase-2L and -3 and the mitochondrial release of cytochrome c without modifying the expression of Bcl-2 and Bcl-2-related proteins.…”
Section: Introductionmentioning
confidence: 86%
“…Here, we show that overexpression of p27 Kip1 in leukemic cells growing in suspension delays druginduced apoptosis and cytotoxicity, indicating that neither intercellular adhesion nor adherence to extracellular matrix (Cardone et al, 1997) are necessary for p27 Kip1 to prevent cell death. We also demonstrate that p27 Kip1 overexpression prevents the activation of procaspase-2L and -3 and the mitochondrial release of cytochrome c without modifying the expression of Bcl-2 and Bcl-2-related proteins.…”
Section: Introductionmentioning
confidence: 86%
“…Caspases can cleave not only their death substrates but a variety of signal transduction components including upstream kinases in the JNK/p38 cascades. They include PAK2 (Rudel and Bokoch, 1997), MST1 (Graves et al, 1998) and MEKK1 (Cardone et al, 1997) which are activated upon cleavage of their regulatory domains by caspases. Although the functional signi®cance of activation of these kinases is still unclear, it is suggested that caspase-mediated activation of these kinases may enhance apoptosis and mediate certain phenotypes of apoptotic cells in a JNKdependent and -independent manners, respectively.…”
Section: Jnk Pathways In Cytokine-induced Apoptosismentioning
confidence: 99%
“…The evidence that the JNK pathway is pro-apoptotic derives from studies that show that these kinases are activated rapidly in cells destined to undergo an apoptotic response, that their overexpression results in apoptosis in some cells, that anti-sense inhibition or the use of dominant negative constructs attenuates the apoptotic response, and in a recent publication by the use of a knock-out mouse Brenner et al, 1997;Butter®eld et al, 1997;Cardone et al, 1997;Chen et al, 1996a,b;Chuang et al, 1997;Frisch et al, 1996;Goillot et al, 1997;Seimiya et al, 1997;Verheij et al, 1996;Xia et al, 1995;Yang et al, 1997a;Zanke et al, 1996). In the latter studies, in mice de®cient in JNK3, which is restricted to the brain, there was a reduction in seizure activity and hippocampal apoptosis in response to the excitotoxic glutamate-receptor agonist kainic acid (Yang et al, 1997a).…”
Section: Jnks and Apoptosismentioning
confidence: 99%